Low-loss MnZn ferrite material for 500kHz and preparation method thereof

By using the combined sintering process of CaTiO3 and MnZn ferrite particles in the high frequency band, a high resistance layer is formed, which solves the problem of high loss of MnZn ferrite materials at 500kHz, and achieves low loss and efficient magnetic performance improvement. It is suitable for High-frequency equipment such as new energy vehicles.

CN119170371AActive Publication Date: 2024-12-20SHANDONG UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411324599.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-20
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing MnZn ferrite materials have high losses in the high frequency band (500kHz), and the preparation process takes a long time and energy consumption, making it difficult to meet the needs of high-frequency equipment such as new energy vehicles.

Method used

CaTiO3 is used as an auxiliary component and MnZn ferrite particles to stir and dry in ethanol and press into a magnetic ring, and sintered in a nitrogen-oxygen mixture environment to shorten the sintering time and reduce losses, form a high resistance layer and improve magnetic performance.

Benefits of technology

It effectively reduces the loss of MnZn ferrite material, improves the permeability and permeability temperature coefficient, realizes the preparation of low-loss MnZn ferrite material, and reduces production costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170371A_ABST
    Figure CN119170371A_ABST
Patent Text Reader

Abstract

The invention relates to a low-loss MnZn ferrite material for 500kHz and a preparation method of the low-loss MnZn ferrite material. Comprising the following steps: (1) adding MnZn ferrite particles and CaTiO3 powder into ethanol, stirring for 1.5-2.5 hours under the water bath condition of 45-55 DEG C, and drying to obtain mixed powder; and (2) pressing the mixed powder into a magnetic ring, carrying out heat preservation at 1100-1200 DEG C under nitrogen and oxygen mixed gas for 45-75 minutes, and then cooling to 180-220 DEG C, so as to obtain the low-loss MnZn ferrite material for 500kHz. According to the preparation method provided by the invention, CaTiO3 is used as an auxiliary component to modify the MnZn ferrite, the magnetic conductivity is improved, the temperature coefficient of the magnetic conductivity is improved, the eddy-current loss and the magnetic hysteresis loss are reduced, the lowest loss at 500kHz and room temperature is 128 mW.cm <-3 >, and the loss is reduced by 42.1% compared with that of a conventional MnZn ferrite material without CaTiO3; the use loss of the MnZn ferrite material is greatly reduced, and the use performance of the MnZn ferrite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-loss MnZn ferrite material for 500kHz and a preparation method thereof, belonging to the technical field of magnetic material preparation. Background Art

[0002] With the development of new energy vehicles, solar panels, 5G communication technology and the call for green energy saving, low carbon and environmental protection, electronic components such as transformers and inductors are developing in the direction of high frequency, high efficiency, miniaturization and ultra-thinness, which puts forward the demand for low loss at higher frequencies for the soft ferrite materials used. At the same time, most domestic MnZn ferrite manufacturers have excess production capacity, but the added value of their magnetic powder products is low, and the magnetic cores are mostly used in low frequency bands. In order to improve the competitiveness of domestic manufacturers and increase the added value of products, a simple, feasible and effective preparation process is urgently needed to change this situation.

[0003] In order to reduce the total loss of MnZn power ferrite at 500kHz, it is necessary to separate the total loss of the material, analyze its loss composition and proportion, and then take corresponding measures to reduce specific losses, thereby more effectively reducing the total loss of MnZn ferrite materials. Chinese patent document CN117466638A discloses a wide temperature and low loss MnZn ferrite material, which includes a main component and an auxiliary component, wherein the main component is 53.1-53.8 mol% Fe2O3, 9-10 mol% ZnO, and the balance is MnO, and the auxiliary component is composed of: 0.34-0.45wt% Co2O3, 0.03-0.04wt% CaCO3, 0.020-0.025wt% Nb2O5, 0.01-0.02wt% ZrO2, 0.003-0.006wt% SiO2, 0.05-0.5wt% NiO, and 0.1-0.2wt% SnO2. However, the MnZn ferrite material provided by the patent does not involve losses in the higher frequency band (500kHz), and the dopant needs to be added during the secondary ball milling. Once the doping effect is lower than expected, re-mixing will result in a waste of material time, and the sintering process of this method requires a 3-hour insulation time, which has high energy consumption.

[0004] Therefore, the development of a MnZn ferrite material that can be used in the 500kHz high frequency band and maintain low loss, as well as a preparation method with a simpler and more effective doping method, a shorter sintering process and lower energy consumption, is of great significance to the entire production and application of MnZn ferrite materials. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a low-loss MnZn ferrite material for 500 kHz and a preparation method thereof.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a low-loss MnZn ferrite material for 500kHz comprises the following steps:

[0008] (1) adding MnZn ferrite particles and CaTiO3 powder to ethanol, stirring for 1.5 to 2.5 hours in a water bath at 45 to 55° C., and drying to obtain a mixed powder;

[0009] (2) The mixed powder is pressed into a magnetic ring at 300-500 MPa, and then the magnetic ring is placed in a sintering device, kept at 1100-1200° C. in a nitrogen-oxygen mixed gas for 45-75 minutes, and then cooled to 180-220° C. to obtain a low-loss MnZn ferrite material for 500 kHz.

[0010] Preferably, in step (1), the mass ratio of the MnZn ferrite particles to the CaTiO3 powder is 1000:(0.4-1.2). The MnZn ferrite particles are existing materials and can be prepared according to a known method or obtained commercially.

[0011] Further preferably, the mass ratio of the MnZn ferrite particles to the CaTiO3 powder is 1000:1.

[0012] Preferably according to the present invention, in step (1), the mass volume ratio of the MnZn ferrite particles to ethanol is 65:(80-120), unit: g / mL.

[0013] Preferably according to the present invention, in step (1), the temperature of the water bath is 50° C., the stirring time is 2 h, and the stirring rate is 300 r / min.

[0014] Preferably, according to the present invention, in step (1), the drying is carried out in an oven at 80° C. for 45 to 75 minutes.

[0015] Preferably according to the present invention, in step (2), the sintering temperature is 1150° C. and the holding time is 60 min.

[0016] Preferably, according to the present invention, in step (2), the oxygen content in the nitrogen-oxygen mixed gas is 3.5%, a nitrogen-oxygen mixer is used to maintain the oxygen content during the insulation process, and flowing nitrogen is filled into the sintering equipment during the cooling process until the cooling is completed.

[0017] The present invention also provides a low-loss MnZn ferrite material for 500 kHz prepared by the method.

[0018] Anything not described in detail in the present invention can be carried out according to the prior art.

[0019] Technical features and beneficial effects of the present invention:

[0020] 1. In the preparation method provided by the present invention, CaTiO3 is used as an auxiliary component to modify MnZn ferrite, wherein Ca 2+ The ions form a high resistance layer at the grain boundary, which increases the grain boundary resistivity, makes the grain boundary obvious, refines the grains, and reduces eddy current loss; Ti 4+ Some of them exist at the grain boundary, and some of them enter the crystal lattice. The Ti inside the crystal lattice 4+ This will cause 2Fe to appear at the B site of MnZn ferrite 3+ →Fe 2+ +Ti 4+ The conversion of Fe 2+ (K1>0), and because Ti 4+ The ionic radius is larger than that of Fe 3+ The radius of the MnZn ferrite is large, which changes the magnetic field characteristics of the crystal, making its magnetocrystalline anisotropy have an obvious K1>0 effect, increasing the magnetic permeability and improving the temperature coefficient of magnetic permeability, reducing eddy current loss and hysteresis loss. Therefore, adding CaTiO3 can effectively improve the magnetic properties and microstructure of MnZn ferrite, thereby obtaining MnZn power ferrite that can be used for 500kHz.

[0021] 2. The low-loss MnZn ferrite material provided by the present invention has a minimum loss of 128 mW·cm at 500 kHz and room temperature. -3 Compared with the conventional MnZn ferrite material without adding CaTiO3, the loss is reduced by 42.1%, which greatly reduces the use loss of MnZn ferrite material and improves the use performance of MnZn ferrite material.

[0022] 3. The present invention provides a new method for preparing low-loss MnZn ferrite materials, which can directly adjust the composition based on MnZn ferrite particles, providing a new idea for industrial production. In addition, the doping method can be used to reuse the powder with excess production capacity in industrial production, increase the added value of products, and reduce production losses and costs. At the same time, during the sintering process, it only needs to be kept at 1150°C for 45 to 75 minutes, and there is no need to adjust the sintering temperature multiple times, which is of great significance to energy saving and low carbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD diagrams of the low-loss MnZn ferrite materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0024] The present invention is further described below by specific examples and drawings, but the scope of the present invention is not limited. The raw materials used in the examples are all conventional raw materials, and the equipment used is all conventional equipment, which can be purchased from the market.

[0025] Among them, MnZn ferrite particles are existing materials, which can be prepared according to the "Soft Ferrite Production Process and Control Technology" or obtained from the market.

[0026] Example 1

[0027] A method for preparing a low-loss MnZn ferrite material for 500kHz comprises the following steps:

[0028] (1) Add 65 g of MnZn ferrite particles and 0.026 g of CaTiO3 powder to 100 mL of ethanol, place the container containing the powder and ethanol in a water bath crucible, stir for 2 h in a 50°C water bath at a speed of 300 r / min using an electronic stirring rod until the ethanol is almost completely evaporated, place the stirred powder in an 80°C oven and dry for 60 min until the ethanol is completely evaporated and the powder has good fluidity, then take it out and cool it to room temperature to obtain a mixed powder;

[0029] (2) A hydraulic press is used to press the mixed powder into a magnetic ring at 400 MPa, and then the magnetic ring is placed in a bell-type atmosphere sintering furnace and kept warm for 60 minutes at a sintering temperature of 1150°C and a nitrogen-oxygen mixed gas environment. During the insulation process, a nitrogen-oxygen mixer is used to maintain the oxygen content at 3.5%. The mixture is then cooled to 200°C. During the cooling process, flowing nitrogen is filled into the furnace, and the product is taken out to obtain a low-loss MnZn ferrite material for 500 kHz.

[0030] The low-loss MnZn ferrite material for 500 kHz prepared in this embodiment is numbered 2, denoted as CTO-4.

[0031] Example 2

[0032] A method for preparing a low-loss MnZn ferrite material for 500kHz comprises the following steps:

[0033] (1) Add 65 g of MnZn ferrite particles and 0.052 g of CaTiO3 powder to 100 mL of ethanol, place the container containing the powder and ethanol in a water bath crucible, stir for 2 h in a 50°C water bath at a speed of 300 r / min using an electronic stirring rod until the ethanol is almost completely evaporated, place the stirred powder in an oven at 80°C and dry for 60 min until the ethanol is completely evaporated and the powder has good fluidity, then take it out and cool it to room temperature to obtain a mixed powder;

[0034] (2) A hydraulic press is used to press the mixed powder into a magnetic ring at 400 MPa, and then the magnetic ring is placed in a bell-type atmosphere sintering furnace and kept warm for 60 minutes at a sintering temperature of 1150°C and a nitrogen-oxygen mixed gas environment. During the insulation process, a nitrogen-oxygen mixer is used to maintain the oxygen content at 3.5%. The mixture is then cooled to 200°C. During the cooling process, flowing nitrogen is filled into the furnace, and the product is taken out to obtain a low-loss MnZn ferrite material for 500 kHz.

[0035] The low-loss MnZn ferrite material for 500 kHz prepared in this embodiment is numbered 3, denoted as CTO-8.

[0036] Example 3

[0037] A method for preparing a low-loss MnZn ferrite material for 500kHz comprises the following steps:

[0038] (1) Add 65 g of MnZn ferrite particles and 0.065 g of CaTiO3 powder to 100 mL of ethanol, place the container containing the powder and ethanol in a water bath crucible, stir with an electronic stirring rod for 2 h in a 50°C water bath at a speed of 300 r / min, until the ethanol is almost completely evaporated, place the stirred powder in an 80°C oven and dry for 60 min until the ethanol is completely evaporated and the powder has good fluidity, then take it out and cool it to room temperature to obtain a mixed powder;

[0039] (2) A hydraulic press is used to press the mixed powder into a magnetic ring at 400 MPa, and then the magnetic ring is placed in a bell-type atmosphere sintering furnace and kept warm for 60 minutes at a sintering temperature of 1150°C and a nitrogen-oxygen mixed gas environment. During the insulation process, a nitrogen-oxygen mixer is used to maintain the oxygen content at 3.5%. The mixture is then cooled to 200°C. During the cooling process, flowing nitrogen is filled into the furnace, and the product is taken out to obtain a low-loss MnZn ferrite material for 500 kHz.

[0040] The low-loss MnZn ferrite material for 500 kHz prepared in this embodiment is numbered 4, denoted as CTO-10.

[0041] Example 4

[0042] A method for preparing a low-loss MnZn ferrite material for 500kHz comprises the following steps:

[0043] (1) Add 65 g of MnZn ferrite particles and 0.078 g of CaTiO3 powder to 100 mL of ethanol, place the container containing the powder and ethanol in a water bath crucible, stir for 2 h in a 50°C water bath at a speed of 300 r / min using an electronic stirring rod until the ethanol is almost completely evaporated, place the stirred powder in an oven at 80°C and dry for 60 min until the ethanol is completely evaporated and the powder has good fluidity, then take it out and cool it to room temperature to obtain a mixed powder;

[0044] (2) A hydraulic press is used to press the mixed powder into a magnetic ring at 400 MPa, and then the magnetic ring is placed in a bell-type atmosphere sintering furnace and kept warm for 60 minutes at a sintering temperature of 1150°C and a nitrogen-oxygen mixed gas environment. During the insulation process, a nitrogen-oxygen mixer is used to maintain the oxygen content at 3.5%. The mixture is then cooled to 200°C. During the cooling process, flowing nitrogen is filled into the furnace, and the product is taken out to obtain a low-loss MnZn ferrite material for 500 kHz.

[0045] The low-loss MnZn ferrite material for 500 kHz prepared in this embodiment is numbered 5, denoted as CTO-12.

[0046] Comparative Example 1

[0047] A method for preparing a MnZn ferrite material, the steps are as described in Example 1, except that no CaTiO3 powder is added in step (1).

[0048] The MnZn ferrite material prepared in this comparative example is numbered 1 and is recorded as CTO-0.

[0049] Test example

[0050] XRD characterization and performance testing were performed on the products prepared in Examples 1 to 4 and Comparative Example 1. The test indicators included initial magnetic permeability (μ i ) and loss (P cv ), the result is as follows Figure 1 And as shown in Table 1.

[0051] The specific test method is: use LCR meter to test its inductance value and calculate its initial magnetic permeability μ i , use the power consumption meter to test its loss P at 500kHz and 50mT cv .

[0052] Table 1. Product performance of Examples 1 to 4 and Comparative Example 1

[0053]

[0054] Depend on Figure 1It can be seen that after sintering, Examples 1 to 4 and Comparative Example 1 have only one physical phase, MnZn ferrite, which indicates that the present invention successfully prepares MnZn ferrite material and the doped CaTiO3 does not affect the composition of the physical phase.

[0055] As shown in Table 1, compared with Comparative Example 1, the losses of the MnZn ferrite materials prepared in Examples 1 to 4 at 500kHz and 50mT are significantly reduced. In particular, the loss of the MnZn ferrite material No. 4 (CTO-10) is the lowest, which is only 128mW·cm -3 Compared with the conventional MnZn ferrite material without CaTiO3 (Comparative Example 1), the loss is reduced by 42.1%, which can be compared with the performance of the PC500 product of Japan TDK Company under the same test conditions. It shows that the preparation method provided by the present invention uses CaTiO3 as an auxiliary component to modify the MnZn ferrite, wherein Ca 2+ The ions form a high resistance layer at the grain boundary, which increases the grain boundary resistivity, makes the grain boundary obvious, refines the grains, and reduces eddy current loss; Ti 4+ Some of them exist at the grain boundary, and some of them enter the crystal lattice. The Ti inside the crystal lattice 4+ This will cause 2Fe to appear at the B site of MnZn ferrite 3+ →Fe 2+ +Ti 4+ The conversion of Fe 2+ (K1>0), and because Ti 4+ The ionic radius is larger than that of Fe 3+ The radius is large, which changes the magnetic field characteristics of the crystal, making its magnetocrystalline anisotropy have an obvious K1>0 effect, increasing the magnetic permeability and improving the temperature coefficient of magnetic permeability, reducing eddy current loss and hysteresis loss. Adding CaTiO3 can effectively improve the magnetic properties and microstructure of MnZn ferrite materials, thereby obtaining MnZn power ferrite that can be used for 500kHz.

[0056] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify or replace the technical solution of the present invention with equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a low-loss MnZn ferrite material for 500kHz, It is characterized in that The steps include: (1) MnZn ferrite particles and CaTiO 3 The powder is added to ethanol, stirred in a water bath at 45-55°C for 1.5-2.5 hours, and dried to obtain a mixed powder; (2) The mixed powder is pressed into a magnetic ring at 300-500 MPa, and then the magnetic ring is placed in a sintering device, kept at 1100-1200° C. in a nitrogen-oxygen mixed gas for 45-75 minutes, and then cooled to 180-220° C. to obtain a low-loss MnZn ferrite material for 500 kHz.

2. The preparation method according to claim 1, It is characterized in that In step (1), the MnZn ferrite particles and CaTiO 3 The mass ratio of the powder is 1000:(0.4~1.2).

3. The preparation method according to claim 2, It is characterized in that The MnZn ferrite particles and CaTiO 3 The mass ratio of the powder is 1000:

1.

4. The preparation method according to claim 1, It is characterized in that In step (1), the mass volume ratio of the MnZn ferrite particles to ethanol is 65:(80-120), unit: g / mL.

5. The preparation method according to claim 1, It is characterized in that In step (1), the temperature of the water bath is 50° C., the stirring time is 2 h, and the stirring rate is 300 r / min.

6. The preparation method according to claim 1, It is characterized in that In step (1), the drying step is performed by placing the product in an oven at 80° C. for 45 to 75 minutes.

7. The preparation method according to claim 1, It is characterized in that In step (2), the sintering temperature is 1150° C. and the holding time is 60 min.

8. The preparation method according to claim 1, It is characterized in that In step (2), the oxygen content in the nitrogen-oxygen mixed gas is 3.5%. During the heat preservation process, a nitrogen-oxygen mixer is used to maintain the oxygen content. During the cooling process, flowing nitrogen is filled into the sintering equipment until the cooling is completed.

9. A low loss MnZn ferrite material for 500kHz, It is characterized in that It is prepared according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composite material, and method for manufacturing the same

    CN101981631A

  • Ultralow-high-frequency-loss-power MnZn ferrite and preparation method thereof

    CN102976739A

  • Nonmagnetic ceramics

    JP1993319896A

  • Method for manufacturing wide-temperature low-loss high-bs manganese-zinc ferrite material

    WO2023130731A1